Criteria for NPP industrial site flooding by combined impact of tornadoes and earthquakes in the cooling pond - Козлов, Игорь Леонидович (Eastern-European Journal of Enterprise Technologies, 2015)
The results of analysis of the impact of extreme natural phenomena on safety of nuclear power plants in Ukraine, held in the "pre" and "post-Fukushima" periods have shown that tornadoes and earthquakes are the most likely events. However, the results are contradictory in relation to probability assessment of security-critical tornadoes, and do not take into account the possibility of the NPP industrial site flooding under the combined effect of tornadoes and earthquakes in the station reservoirs. Hydrodynamic model of NPP industrial site flooding wave during tornadoes and earthquakes, based on the assumption of the flooding wave formation under the influence of tornado lift and seismic shock, as well gravity and internal dissipation forces; cylindrical shape of the flooding wave; conservative isothermal exposure of the flooding wave near the coast was developed. The flooding wave emergence and development process is conventionally divided into two different time-scale phases: the initial phase of the combined (in general) earthquake and tornado, the final stage of the tornado impact. Based on the developed hydrodynamic model, deterministic criteria of possible NPP industrial site flooding at the combined (in general) impact of the tornado and earthquake in the cooling pond were defined. The analysis was performed on the example of the Zaporizhzhya NPP, due to which it was found that there was no flooding under tornadoes below the 2-intensity grade and earthquakes with response acceleration at the cooling pond bottom of less than 10 m/s2 and duration of about ten seconds.